The Effect of CSR Disclosure on Firm Value with Profitability and Leverage as Moderators - Putu Pande R. Aprilyani Dewi; I Putu Sudana; I Dewa Nyoman Badera; I Ketut Rasmini (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study determines the effect of the corporate social responsibility (CSR) disclosure on firm value. The population of this study is composed of mining companies listed on the Indonesian Stock Exchange from 2016 to 2018. The study used a purposive sampling technique and obtained a sample of 66 companies. Applying moderated regression analysis, the results indicate a positive effect of CSR disclosure on firm value. Furthermore, profitability strengthens this effect on firm value, whereas leverage weakens it. CSR disclosure and its interaction with leverage reveal an influence on firm value. The lower the level of the leverage ratio of a company, the higher the CSR disclosure conducted by it, which subsequently increases firm value. This study contributes to business professionals by confirming that firm value will rise with increased CSR disclosure in financial reports.